Pengaruh Influencer Janes Christina dan Kualitas Produk Kosmetik Somethinc terhadap Keputusan Pembelian pada Aplikasi Tiktok - Aimmatul Khulwani; Citra Savitri; Syifa Pramudita Faddila (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The growth of the industrial sector in Indonesia is currently still a pillar of the country's economy, one of which is the cosmetics industry. Interest in seeking beauty in Karawang Regency has fluctuated. The purpose of this research is to examine the influence of the role of influencers and product quality in influencing the decision to buy cosmetics Something on TikTok. This study uses a quantitative method with the Partial Least Square-Structural Equal Model (PLS-SEM) approach. The population of this research is women belonging to Generation Z who follow Janes Christina's tiktok account and have used Somethinc cosmetic products for as many as 128 people and a sample of 100 people. Data collection uses a questionnaire via Google form and the analysis tool uses SmartPLS 3.0 software to test the proposed hypothesis. Based on the results of the study, researchers found that influencers and product quality had a positive and significant effect on purchasing decisions. Keywords: Author Guidelines; Influencer, Product Quality, Purchase Decision